If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -8 + 6f = 10 + 6f Reorder the terms: -8 + 3f + 6f = 10 + 6f Combine like terms: 3f + 6f = 9f -8 + 9f = 10 + 6f Solving -8 + 9f = 10 + 6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6f' to each side of the equation. -8 + 9f + -6f = 10 + 6f + -6f Combine like terms: 9f + -6f = 3f -8 + 3f = 10 + 6f + -6f Combine like terms: 6f + -6f = 0 -8 + 3f = 10 + 0 -8 + 3f = 10 Add '8' to each side of the equation. -8 + 8 + 3f = 10 + 8 Combine like terms: -8 + 8 = 0 0 + 3f = 10 + 8 3f = 10 + 8 Combine like terms: 10 + 8 = 18 3f = 18 Divide each side by '3'. f = 6 Simplifying f = 6
| 19x-16x=45-60 | | 7-7x=87-35x | | -15-6x=5-8x | | -88-7x=9x+24 | | 5-w=2w-1 | | 2x+11=-19-8x | | 94-4x=2x+16 | | -9h+10=-5h-10 | | 6x+10=28 | | 17x=2(8x-4) | | -9-6d-9=-9d+9 | | 5-b=6b+5-7b | | T(10)=6n-4 | | 9+11x=119+x | | 12x^2-26x+8=0 | | 3t+10t+8=0 | | -q-9=-q-3q+6 | | 3x+5=2x+10 | | V(5)=7*3.14r^2 | | 3x+8=4x-3 | | 2x+35=x+70 | | 10x-7=8x+3 | | -9s=7-10s | | -22=3s+-8 | | 8d-2=10d | | 4(2a+3)=20 | | -10+y=10-3y | | 5y=x-7 | | 17=5-x | | 12-4x-6=2x+14 | | -7c=-6-5c | | 5y=-7+x |